One treble evening in Sahara - Kombat of the Pilgrims; KOMBAT; PonyCanyon Music (M). (Kuala Lumpur : PonyCanyon Music (M), 1998)
Terdapat tujuh belas buah lagu berkonsepkan'Instrument Guitar Jamming' yang dimuatkan dalam album ini.
CD 1 : Message From Mars (3:14) -- Kamananna (2:39) -- Memories of Madrid (2:45) -- Big Kahuna (1:50) -- Plastic for 500, Bob! (1:50) -- The Exotic Dance Manifesto (2:45) -- Monster Freak'theme' (1:35) -- Saudagar Unta (3:10) -- One Night in Beirut (3:30) -- Buah Qurma (3:00) -- Laguna Beach (1:55) -- La Bambora (2:13) -- Layale (2:35) -- Walk don't Run, but Fly! (2:13) -- Alexandria (3:33) -- Going My Wave (1:55) -- Misirlou (5:52).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs with guitar